An Empirical Assessment of Organizational Commitment Using the Side-Bet Theory Approach - Cohen, Aaron; Gattiker, Urs (Relations industrielles / Industrial Relations, 1992)
According to the side-bet theory, organizational commitment increases with the accumulation of side bets or investments. Cross-national data for seven side-bet indexes (age, tenure, education, marital status, salary, gender, and hierarchical position) were used to test the theory's generalizability. Four hundred and sixty-three white-collar employees in Canada and the U.S. were surveyed. The findings indicated that while organizational commitment levels between Canadian and U.S. respondents were similar, the effects of various side-bet indexes differed between the two countries. The results suggest that previously reported correlations between age, tenure and organizational commitment (e.g. Meyer and Allen 1984) cannot be replicated. The results are discussed in terms of their implications for future investigation of the side-bet theory and organizational commitment.